The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1161/01.cir.102.15.1802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antihypertensive Therapy on Glucose and Insulin Metabolism and on Left Ventricular Mass

Abstract: In obese, hypertensive individuals, adequate and similar blood pressure control was achieved with perindopril and atenolol. However, perindopril but not atenolol was associated with a more favorable GIM profile and led to a significant regression of LVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…The results of several experimental and clinical studies indicate that angiotensin-converting-enzyme inhibitor effectively reduces left ventricular hypertrophy [Black et al 1996, Kobayashi et al 1990]. In comparison with other antihypertensive drugs, perindopril signifi cantly prevents the development of left ventricular hypertrophy in hypertensive patients and laboratory rats [Black et al 1996, Kuperstein andSasson 2000, C -control group, PR -group with perindopril, MT -group with metoprolol, ID -group with indapamide, AM -group with amlodipine, WBC -white blood cells, RBC -red blood cells, HGB -hemoglobin, HCT -hematocrit, Lym -lymphocytes, n -number of rats in the group. *Signifi cantly differences vs C group.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several experimental and clinical studies indicate that angiotensin-converting-enzyme inhibitor effectively reduces left ventricular hypertrophy [Black et al 1996, Kobayashi et al 1990]. In comparison with other antihypertensive drugs, perindopril signifi cantly prevents the development of left ventricular hypertrophy in hypertensive patients and laboratory rats [Black et al 1996, Kuperstein andSasson 2000, C -control group, PR -group with perindopril, MT -group with metoprolol, ID -group with indapamide, AM -group with amlodipine, WBC -white blood cells, RBC -red blood cells, HGB -hemoglobin, HCT -hematocrit, Lym -lymphocytes, n -number of rats in the group. *Signifi cantly differences vs C group.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 CCBs are known to be metabolically neutral, 30,31 and long-acting dihydropyridines CCBs have been reported to improve glucose tolerance and lower insulin levels. 32,33 Our results showed that fasting BG and LDL-C were significantly increased in hypertensive patients who received combination therapy of nitrendipine and atenolol, whereas insulin sensitivity and postprandial BG were not significantly articles Metformin Prevents a β-Blocker-Induced Weight Gain changed, suggesting that the mechanism of combination therapy of nitrendipine and atenolol in deteriorating BG and BL may be related to the action of atenolol.…”
Section: Metformin Prevents a β-Blocker-induced Weight Gainmentioning
confidence: 99%
“…It should be noted that high doses, for example, perindopril Various studies have shown that ACE inhibitors significantly 8mg were required to improve carotid structure and function in reduce LV mass index (LVMI) in patients with hypertension; [48][49][50][51][52][53] hypertensive patients with type 2 diabetes mellitus. The beneficial an effect which takes place within a few months of initiating effect of perindopril on arterial stiffness observed in the 3-month treatment with an ACE inhibitor and is seen to a greater extent study [65] was unlikely to have been the result of vascular remodelwith ACE inhibitors than other CCA [50] or β-blockers.…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…The beneficial an effect which takes place within a few months of initiating effect of perindopril on arterial stiffness observed in the 3-month treatment with an ACE inhibitor and is seen to a greater extent study [65] was unlikely to have been the result of vascular remodelwith ACE inhibitors than other CCA [50] or β-blockers. [49,52,53] ing, because of rapid onset of action and loss of effect after Beneficial effects on endothelial function have been observed discontinuation of therapy, and it is possible that the effect was after long-term use of various ACE inhibitors, [54][55][56][57][58][59][60][61][62] including attributable to improved endothelial function. Indeed, ACE inhibiperindopril.…”
Section: Cardiac Remodelingmentioning
confidence: 99%